2018
DOI: 10.1007/s10143-018-0961-1
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Meningiomas Prognostic Evaluation Score (SPES): predicting the neurological outcomes in spinal meningioma surgery

Abstract: Among many factors leading to a worse functional prognosis in spinal meningioma (SM) surgery, in a previous study, we recognized anterior/anterolateral axial topography, sphincter involvement at first evaluation, surgery performed on a recurrence, and worse preoperative functional status. The purpose of this paper is to evaluate the cumulative weight of these factors on prognosis through a multinomial logistic regression model performed on an original evaluation scale designed by the authors on the ground of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 37 publications
3
20
0
Order By: Relevance
“…The most common axial location in our series was ventrolateral (12 patients, 54.5%); dorsolateral location was represented in 4 patients (18.2%). As previously reported by other authors, the ventral/ventrolateral topography is a quite common location for the dural attachment of the spinal meningiomas (38.5-65.2%) 3,9) . The meningothelial type (14 patients, 63.7%) of meningioma was the most common histology subtype in our series, followed by psammomatous in 4 patients (18.2%).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The most common axial location in our series was ventrolateral (12 patients, 54.5%); dorsolateral location was represented in 4 patients (18.2%). As previously reported by other authors, the ventral/ventrolateral topography is a quite common location for the dural attachment of the spinal meningiomas (38.5-65.2%) 3,9) . The meningothelial type (14 patients, 63.7%) of meningioma was the most common histology subtype in our series, followed by psammomatous in 4 patients (18.2%).…”
Section: Discussionsupporting
confidence: 80%
“…The most common presenting symptoms were paresthesia (15 patients, 68.2%) in our series and the mean duration of symptoms before presentation was 11.2±20.5 months. Majority of prior reports of spinal meningiomas 3,5,10,15) informed similar predominant symptom and duration. Also, prior studies reported 26.3% to 51% of bladder and sphincter disturbances, but our series showed no significant difference in bladder and sphincter disturbances.…”
Section: Discussionmentioning
confidence: 82%
“…The poor functional outcome of those patients in our study having a baseline myelomalacia sign might be explained by the majority having a late stage or advance stage myelomalacia (25). Frati et al (34) developed an interesting score predicting the neurological outcome in a retrospective series investigating 173 spinal meningioma cases. This study identified anterior location, operating on a recurrent SM, sphincter involvement, and worse functional grade at onset as potential predictors of the functional outcome.…”
Section: Review Of Predictors Of Functional Outcomementioning
confidence: 77%
“…It is widespread opinion, corroborated by evidence, that clinical status of patients with spinal cord tumors usually benefits from early surgery. The early recognition of signs and symptoms, that allows diagnosis of early-stage disease before spinal cord damage occurs, can reduce the risk of postoperative morbidity and may improve surgical outcome (29)(30)(31). A strong correlation has been suggested between the degree of functional impairment and the extent of damage to the spinal cord or spinal roots: the greater the impairment, the longer the persistence of the lesion, and the more difficult postoperative functional recovery will be, despite radical tumor removal (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%